Romans 1:24–28 and Same-Sex Practice: Some Exegetical Remarks - Nel, Marius (Religions, 2025)
Few things can potentially divide (and are dividing) Christians like the LGBTIQ+ issue. Conservative churches argue that sexuality forms an integral part of the human being and, hence, that sexual sin falls in a category of its own in any catalogue of sins. It is sin committed in the human body that radically affects one’s participation in Christ’s earthly body. To act on the realisation of same-sex lust is in itself sinful. Same-sex practices are viewed as sexual sin and all practitioners are condemned. On the other hand, there are Christians who accept that a homosexual orientation can be a biological given that needs to be accepted but that God views homosexual practice as an evil that should be avoided at all costs. Then there are also Christians who accept that a homosexual orientation is integral to some people’s humanity and accept same-sex behaviour as a regular expression of sexuality. Romans 1 plays a key role in the church’s discussion of the issue. The article reconsiders the textual evidence, using an exegetical model based on the historical–critical method combined with biblical theology. The conclusion is that Romans 1:24–29 refers to same-sex behaviour within the context of the Gentile world of idolatry that engages in wilful transgression of God’s bounds, resulting in degeneration in the lives of offenders.